Comparison of the Proteome of Adult and Cord Erythroid Cells, and Changes in the Proteome Following Reticulocyte Maturation - Wilson, Marieangela C. (Mol Cell Proteomics, 2016)
Cord blood stem cells are an attractive starting source for the production of red blood cells in vitro for therapy because of additional expansion potential compared with adult peripheral blood progenitors and cord blood banks usually being more representative of national populations than blood donors. Consequently, it is important to establish how similar cord RBCs are to adult cells. In this study, we used multiplex tandem mass tag labeling combined with nano-LC-MS/MS to compare the proteome of adult and cord RBCs and reticulocytes. 2838 unique proteins were identified, providing the most comprehensive compendium of RBC proteins to date. Using stringent criteria, 1674 proteins were quantified, and only a small number differed in amount between adult and cord RBC. We focused on proteins critical for RBC function. Of these, only the expected differences in globin subunits, along with higher levels of carbonic anhydrase 1 and 2 and aquaporin-1 in adult RBCs would be expected to have a phenotypic effect since they are associated with the differences in gaseous exchange between adults and neonates. Since the RBC and reticulocyte samples used were autologous, we catalogue the change in proteome following reticulocyte maturation. The majority of proteins (>60% of the 1671 quantified) reduced in abundance between 2- and 100-fold following maturation. However, ∼5% were at a higher level in RBCs, localized almost exclusively to cell membranes, in keeping with the known clearance of intracellular recycling pools during reticulocyte maturation. Overall, these data suggest that, with respect to the proteome, there is no barrier to the use of cord progenitors for the in vitro generation of RBCs for transfusion to adults other than the expression of fetal, not adult, hemoglobin.